Rhinovirus-induced alterations on peripheral blood mononuclear cell phenotype and costimulatory molecule expression in normal and atopic asthmatic subjects - Papadopoulos, N. G.; Stanciu, L. A.; Papi, A.; Holgate, S. T.; Johnston, S. L. (Clin Exp Allergy, 2002)
Rhinovirus (RV) infection is the commonest trigger of acute asthma exacerbations; however, the immune response to these viruses and any potential implications in the mechanisms leading to asthma exacerbations are not well understood.|To assess the effects of in vitro RV infection on the phenotype and expression of costimulatory molecules on peripheral blood mononuclear cells (PBMC) from normal and atopic asthmatic subjects, as a model for RV antigen presentation.|PBMC from seven normal and seven asthmatic subjects were exposed to one infectious unit/cell of RV16 for 48 h. Surface expression of CD25, CD28, CD40, CD54, CD80, CD86 and CTLA-4 was evaluated on CD3, CD4, CD8, CD14 and CD19 PBMC subpopulations by three-colour flow cytometry.|No changes in the percentage of CD3, CD4, CD8 or CD19 were observed. CD14 was significantly reduced by the infection and this was more pronounced in normal subjects. On Th cells CTLA-4 was increased after RV infection only in the asthmatic group. Levels of CD80 and CD86 in the control cultures were lower in the asthmatic group. RV infection induced a significant increase of CD80 on monocytes and of CD86 on B cells, which occurred in both groups but were less marked in atopic asthmatic subjects.|Exposure of PBMC to RV is able to activate the antigen presentation machinery. Differences between normal and atopic asthmatic individuals are compatible with the hypothesis that an aberrant immune response to RV may be involved in the development of acute exacerbations in atopic asthmatic subjects.
Keywords: Adult Antigen Presentation Antigens; CD Asthma Female Humans Hypersensitivity; Immediate Immunophenotyping Leukocytes; Mononuclear Male Middle Aged Rhinovirus